Rancang Bangun Sistem Informasi Rental Mobil Terintegrasi Whatsapp API Gateway - Muhammad Akhyar; Iskandar Zulkarnaini; Iqbal (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
This study aims to design and implement a web-based car rental information system integrated with a WhatsApp API Gateway to improve operational efficiency and customer communication. The background of this research is the use of manual systems in rental services, which often leads to delays, data recording errors, and ineffective information delivery. The development method used is the Waterfall model, consisting of requirement analysis, system design, implementation, and testing stages. The system is developed using PHP as the programming language and MySQL as the database management system. System functionality is evaluated using Black Box Testing to ensure that all features operate according to user requirements. The results show that the system successfully automates key processes such as user registration, vehicle booking, transaction management, and notification delivery. Furthermore, the integration with WhatsApp API Gateway enables automatic message delivery with a success rate of 100% and a response time of less than 10 seconds. The implementation of this system significantly improves service efficiency, reduces human error, and enhances the quality of communication between service providers and customers.